The Private Placement of Debt and Outside Equity as an Information Revelation Mechanism - Habib, Michel A.; Bruce Johnsen, D. (Review of Financial Studies, 2000)
We view debt and outside equity as serving to elicit credible information from different specialists about the value of an enterprise in its various uses. The equity valuation specialist provides a price forecast for equity that reveals information about the value of the enterprise in its primary use. The debt valuation specialist provides a price forecast for debt that reveals information about the value of the enterprise in its alternative use. The prices forecast by the valuation specialists credibly reveal their private information because they are required to buy the associated claims at the forecast prices, thereby bonding their valuations.